Dalitz plot analysis of B0 → D[bar]0π+π- decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The resonant substructures of B0→¯D0π+π− decays are studied with the Dalitz plot technique. In this study a data sample corresponding to an integrated luminosity of 3.0 fb−1 of pp collisions collected by the LHCb detector is used. The branching fraction of the B0→¯D0π+π− decay in the region m(¯D0π±)>2.1 GeV/c2 is measured to be (8.46±0.14±0.29±0.40)×10−4, where the first uncertainty is statistical, the second is systematic and the last arises from the normalization channel B0→D∗(2010)−π+. The π+π− S-wave components are modeled with the isobar and K-matrix formalisms. Results of the Dalitz plot analyses using both models are presented. A resonant structure at m(¯D0π−)≈2.8 GeV/c2 is confirmed and its spin-parity is determined for the first time as JP=3−. The branching fraction, mass and width of this structure are determined together with those of the D∗0(2400)− and D∗2(2460)− resonances. The branching fractions of other B0→¯D0h0 decay components with h0→π+π− are also reported. Many of these branching fraction measurements are the most precise to date. The first observation of the decays B0→¯D0f0(500), B0→¯D0f0(980), B0→¯D0ρ(1450), B0→D∗3(2760)−π+ and the first evidence of B0→¯D0f0(2020) are presented.
Im Titel sind "0", "+" und "-" hochgestellt
Im Titel ist "D" mit einem Oberstrich dargestellt
The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Gesehen am 27.07.2021